The principles of representative government - Manin, Bernard (Cambridge ; New York : Cambridge University Press, 1997)
Bernard Manin's challenging book defines the key features of modern democratic institutions. For us representative government has come to seem inseparable from democracy. But its modern history begins, as Professor Manin shows, as a consciously chosen alternative to popular self-rule. In the debates which led up to the new constitution of the United States, for the first time, a new form of republic was imagined and elaborated, in deliberate contrast to the experiences of ancient republics from Athens to Renaissance Italy. The balance between aristocratic and democratic components within this novel state form was not, as has been widely supposed, a consequence of a deliberate mystification of its real workings; it was a rationally planned aspect of its basic structure.
Includes bibliographical references and index.
Keywords: Representative government and representation